Catholic Academic Masculinity and Catholic Academic Women in Germany, 1900-1914 - Zwicker, Lisa Fetheringill (The catholic historical review, 2019)
In contrast to the male-only world of most of German student life, when Catholic women entered universities in the early twentieth century, they played an important role in what had been male-only Catholic student organizations. What accounts for the differences between Catholic and non-Catholic student subcultures? In this article, I argue that Catholic constructions of masculinity shaped the support for the integration of the first generation of Catholic women students within Catholic student subculture. In this way, this evidence contributes to research on the ways that constructions of masculinity impacted the experiences of men and women.